ANALISIS KASUS PEMBANTAIAN MY LAI DARI SUDUT PANDANG HUKUM HUMANITER INTERNASIONAL DAN HAM INTERNASIONAL - Ni Luh Mutiara Cahya Dewi (Universitas Pendidikan Ganesha, 2022)
This research was made with the aim of analyzing the My Lai Case that occurred in Vietnam from the point of view of International Humanitarian Law, because the case occurred as a result of the war between Vietnam and the United States which resulted in the United States committing serious international human rights violations and including war crimes or War Crimes. War crimes are acts that violate the laws of war, acts of attack are usually committed against the military or civilians. The My Lai case was a massacre carried out by the United States army against hundreds of unarmed civilians in South Vietnam on March 16, 1968, the massacre resulted in hundreds of deaths. This action is a violation of the 1949 Geneva Conventions and the 1977 Additional Protocol, with the massacre that indirectly the United States army took the human rights of hundreds of unarmed civilians because in human rights there is a right to life while the United States army snatched that right. The method used is the library method with descriptive presentation and qualitative analysis carried out by researching library materials such as articles, internet sites, newspapers, and books related to the case to be analyzed.